The effectiveness of entrepreneurship education at Universiti Malaysia Kelantan. - Ahmad Hanafi Adnan. (2016)
The purpose of study on the effectiveness of entrepreneurship education at Universiti Malaysia Kelantan is to ensure the successful of UMK entrepreneurship development agenda as well as improve entrepreneurship education to be more holistic at UMK. To explore the demography factor contributing to effectiveness of entrepreneurship education. Five objectives of this research are to explore on the entrepreneurship ecosystem at Faculty of Entrepreneurship and Business, Universiti Malaysia Kelantan, to explore on the attitude and self-involvement among of graduate-entrepreneurs toward entrepreneurship education, to explore the graduate-entrepreneurs challenges to embark in entrepreneurship, and to explore the improvement of entrepreneurship knowledge and skill among graduate-entrepreneurs. Seven variables for this research which are entrepreneurship ecosystem, demography, self-involvement, entrepreneurship challenge, entrepreneurship knowledge, entrepreneurship skill, and entrepreneurship attitude. The raw data was collected by conducting a structured interview with four graduate-entrepreneurs. The data was analysed using qualitative research method since not much is known about the situation in hand, and no information is available on how similar problems or research issues have been solved in the past. The finding showed that all informant agreed upon their improvement on entrepreneurship knowledge, skill and attitude toward entrepreneurship, but entrepreneurship ecosystem, self-involvement and preparation to face entrepreneurship challenges need to be enhance in the future.